Rancang Bangun Sistem Monitoring Suhu Air Pada Kolam Pembesaran Ikan Nila Berbasis IoT - Syamsi, Hans Riadhi; Darmawan, Budi; Budiman, Djul Fikry (Journal of Information System Research (JOSH), 2024)
The tilapia rearing process requires optimal water temperature quality for good growth. The optimal water temperature for tilapia rearing is 26°C - 32°C. Temperatures that are too low or too high can cause growth disorders and even death in tilapia. Manual monitoring of tilapia rearing pond water temperature by the pond owner is often inefficient because it requires regular visits. Based on this problem, this research aims to design an automatic tilapia water temperature monitoring system using Internet of Things (IoT) technology that can work automatically and in real-time. The data used in this research is collected through the reading of the pond water temperature by the DS18B20 temperature sensor installed in the tilapia rearing pond. This monitoring system is designed using ESP32 as the main microcontroller, DS18B20 temperature sensor, heater, relay, and LCD. The results showed that the system succeeded in maintaining the optimal water temperature for tilapia. When the water temperature is below 26°C the heater will automatically turn on to warm the pool water temperature and the heater will automatically turn off when the temperature is above 30°C. The average temperature monitored in this study is 28.90 ° C, with successful notifications sent via telegram bot every five minutes and real-time pond water temperature data via LCD.